Sleepy Sheepy and the sheepover - Cummins, Lucy Ruth; Oswald, Pete (New York : Flamingo Books, 2024)
Sleepy Sheepy is excited for his first sleepover at Grammy and Grampy's house, but when it is time to go to bed he misses home too much to fall asleep.
Booklist, December 2023
School Library Journal, March 2024
K-3
AD490L
Keywords: Sleepovers -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Sheep -- Juvenile fiction; Sleepovers -- Fiction; Grandparent and child -- Fiction; Sheep -- Fiction; Animal fiction